Synthesis and antimicrobial evaluation of some 1,2,4-triazolo[1,5-a]pyridine, pyrimidine sulfonamides and sulfinyl derivatives - Abdel-Motaal, Fatma Fakhry; Raslan, Mohamed Abd-Elmonem (European Journal of Chemistry, 2014)
Several new substituted sulfonamides and sulfinyl compound derivatives were obtained by the reaction of 2-thioxo-1,2,4-triazolo[1,5-a]pyridine and pyrimidine thiol derivatives with (2-chloromethyl)benzimidazole and/or (2-chloromethyl)benzooxazole. Structures of the newly synthesized products have been deduced on the basis of spectral and analytical data. The synthesized compounds were screened for their antimicrobial activity.